2016
DOI: 10.1590/0100-69912016006001
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of urolithiasis consultations in the Paraíba Valley

Abstract: Objective: to know the epidemiological profile of patients with urolithiasis in the Paraíba Valley region, identifying its prevalence and spatial distribution. Method: we conducted a cross-sectional study, by residence location in the Paraíba Valley, on morbidity data due to urolithiasis obtained from the DATASUS, covering the period between 2010 and 2012. We aimed at identifying the general, male and female prevalence of urolithiasis, the distribution by age, type of visit, year season and spatial distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 17 publications
2
22
0
4
Order By: Relevance
“…In most countries, males are predisposed to urolithiasis, with male to female ratio ranging from 1.3 to 5 ( Table 1 , Table 2 , Table 3 ) [2] , [62] , [38] . It may be associated with different dietary habits [48] . Men are more likely to have excessive alcohol and coffee, and consumed more meat than women.…”
Section: Risk Factorsmentioning
confidence: 99%
See 3 more Smart Citations
“…In most countries, males are predisposed to urolithiasis, with male to female ratio ranging from 1.3 to 5 ( Table 1 , Table 2 , Table 3 ) [2] , [62] , [38] . It may be associated with different dietary habits [48] . Men are more likely to have excessive alcohol and coffee, and consumed more meat than women.…”
Section: Risk Factorsmentioning
confidence: 99%
“…However, it has been reported that the ratio is descending in many countries, including China, Japan, Thailand, India, Saudi Arabia and Turkey since 1990s, which meant females are more likely to be affected than before [7] , [21] , [35] , [36] , [39] , [48] , [49] , [50] . In India, the ratio is already below 1, which is in contrast to the previous study results [48] . In Japan, the ratio decreased from 3 (middle-aged group) to 1 (rest of the population) [40] , [51] .…”
Section: Risk Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…One dissimilar result was found in the Paraiba Valley study by Silva and Maciel (2016) in connection with the occurrence of urolithiasis among different sexes, where they showed the prevalence ratio as 0.9 men for every woman with no statistically significant difference between them (p-value being >.05). 9 Regarding occurrence of urolithiasis in different age groups, this study showed the highest occurrence of the problem in the group of 'up to 20 years' for the females. But for the males, the age groups of '41 to 60' and '61 and above' years had the higher occurrence in comparison to other groups.…”
Section: Discussionmentioning
confidence: 62%